Islam as critique: Sayyid Ahmad Khan and the challenge of modernity - Hussain, Khurram (Islam of the global west, 2021)
Prologue -- Introduction -- 1. The language of reform -- 2. Modernism and humanism -- 3. The meaning and end of time -- 4. The viva activa -- 5. Knowledge and wisdom -- Epilogue: Can the Muslim speak? -- Notes -- Bibliography -- Index.